2015
DOI: 10.1111/eci.12480
|View full text |Cite
|
Sign up to set email alerts
|

Stairs instead of elevators at the workplace decreases PCSK9 levels in a healthy population

Abstract: Daily physical activity at the work place is independently associated with a decrease in PCSK9 levels over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
3
18
0
3
Order By: Relevance
“…Therefore, the investigators have considered that exercise is likely to affect LDL-C by modulating PCSK9. Kamani et al [72] found a significant decrease in mean PCSK9 levels and mean LDL-C levels in volunteers after 3 months exercise, and concluded that daily exercise is independently associated with a decrease in PCSK9 levels over time. Rideout et al [73] used C57BL/6 mice as a model, and feed them with high-fat diet, then make them do aerobic exercise.…”
Section: Aerobic Exercise With Lipids and Lipoproteinsmentioning
confidence: 99%
“…Therefore, the investigators have considered that exercise is likely to affect LDL-C by modulating PCSK9. Kamani et al [72] found a significant decrease in mean PCSK9 levels and mean LDL-C levels in volunteers after 3 months exercise, and concluded that daily exercise is independently associated with a decrease in PCSK9 levels over time. Rideout et al [73] used C57BL/6 mice as a model, and feed them with high-fat diet, then make them do aerobic exercise.…”
Section: Aerobic Exercise With Lipids and Lipoproteinsmentioning
confidence: 99%
“…Stair climbing uses 8–10 times the energy requirements of the resting state, which makes stair climbing a vigorous daily PA [13,14,15]. The health benefits of regular stair climbing have been reported, including increased aerobic capacity [16,17], improved lipid profiles [18,19], and fitness and body composition [20]. Regular stair use was associated with lower risk of stroke in men who climbed 20–34 floors per week [21], and reduced risk of lung cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, statins upregulate more efficiently PCSK9 mRNA levels than those of the LDLR (Dubuc et al, 2004), rationalizing the poor incremental LDL-c decreases with increasing statin doses. Mediterranean diet (Richard et al, 2012) and exercise (Kamani et al, 2015) reduce circulating levels of PCSK9, whereas high-fat or fructose-rich diets increase the levels of PCSK9 (for a general review see Cui et al, 2015).…”
Section: Role Of Pcsk9 In Inflammation Sepsis and Viral Infectionsmentioning
confidence: 99%